Innovation in Learning as a Strategy to Improve the Quality of Education. VOL 1: Innovation in Learning as a Strategy to Improve the Quality of Education. VOL 1 - abdul hakimin (Innovative Pedagogy and Education Studies, 2025)
Innovation in learning has become a strategic necessity in improving the quality of education in response to rapid developments in science, technology, and societal demands. This study aims to examine the role of learning innovation as an effective strategy to enhance educational quality through the implementation of student-centered approaches, the integration of technology, and the development of creative and adaptive teaching methods. Using a qualitative descriptive approach, this study analyzes various learning innovation practices applied in educational institutions, including project-based learning, collaborative learning, and digital-based instruction. The findings indicate that learning innovation contributes significantly to improving students’ learning motivation, critical thinking skills, and learning outcomes. In addition, innovative learning practices encourage teachers to continuously improve their pedagogical competencies and adapt to diverse student needs. Therefore, innovation in learning is not only a pedagogical approach but also a strategic effort to ensure sustainable improvement in the quality of education.